Challenges in the Management of Oncologic Wounds: Perspectives of Nurses from a Reference Unit in Amazonas (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To explore the experiences of nurses in the management of neoplastic wounds at a cancer referral unit in the state of Amazonas. Method: This was an observational, descriptive study with a qualitative approach. The sample was selected through convenience sampling. Data collection took place after the project was approved by the Research Ethics Committee of the Amazonas State Oncology Control Center Foundation (Fundação Centro de Controle de Oncologia do Estado do Amazonas – FCECON). Bardin’s Thematic Content Analysis (2011) was used to analyze the participants’ statements, following the phases of pre-analysis, exploration of the material, categorization of statements, and treatment of results, inference, and interpretation. Results: A total of 25 oncology nurses were interviewed. After the interviews and synthesis of the statements, three main topics emerged: common characteristics of neoplastic lesions, the role of nursing in the management of these lesions, and psychosocial aspects affecting nurses working in oncology settings. Conclusion: Despite their preparation and training, the interviewees expressed feelings of helplessness in the face of the complexity of the lesions, as well as anguish, frustration, and negative emotions related to the low likelihood of healing. The main concerns regarding oncologic wounds were related to odor, bleeding, and the size of the lesion.